DIGITAL CONTROL SYSTEMS IN URBAN TRANSPORTATION (International journal of artificial intelligence, 2026)
Urban transportation networks are becoming increasingly dependent on digital control systems to enhance efficiency, safety, and sustainability. This paper examines the role of intelligent transport systems (ITS), real-time traffic management, and IoT-based monitoring in modern cities.